Filmes nanoestruturados de polianilina e argila para aplicação em sensores ambientais - Barros, Anerise de (2011)
In this study the development of environmental sensors began from the fabrication of nanoestrutured films obtained by the technique of Layer-by-Layer (LbL). The films of obtaining a nanocomposite material composed of polyaniline (PAni) and montmorillonite clay nanoparticles using the technique mentioned above, allows a detailed study and essential for this work, wich are for subject to various characterizations, wich include ultraviolet visible spectroscopy (UV-vis), Fourier Transformed Infrared Spectroscopy (FTIR) and Raman, scanning electron microscopy (SEM), is used to visualize the morphological construction of LbL films, X-ray diffraction (XRD), wich allows for characterization and molecular atomic arrangements in solids, atomic interplanar distance and determination of crystal structure, this study uses the technique to check the spacing and thickness of the films and built specially for characterizing the intercalation of polymer and clay in order to get results showing the intercalation of polymer precisely the spaces of lamellar clay. The electrochemical sensor developed here is intend to apply for environmental control in order to detect contaminants in water, such as heavy metals (copper, lead and cadmium). The evaluation of these sensors that are made from nanostructured PAni films and nanoparticles of clay is made from the electrochemical detection by cyclic voltammetry and improved method of stripping square wave voltammetry, for such contaminants in samples of knows concentrations. The LbL films made in this work show quite interesting results, highlighting the partial intercalation of PAni in the interlamelar spaces of Clay (characterized by XRD) and the heavy metal detection by voltammetry.